Crystal structure of (E)-7-methoxy-2-((6-methoxypyridin-3-yl)methylene)-3,4-dihydronaphthalen-1(2H)-one, C18H17NO3 - Wang Lei; Meng Qing-Guo; Jiang Nan; Wei Lin; Wang Chun-Hua (Zeitschrift für Kristallographie - New Crystal Structures)
C18H17NO3, monoclinic, P21/n (no. 14), a = 14.702(3) Å, b = 7.0421(11) Å, c = 15.303(3) Å, β = 113.32(2)°, V = 1454.9(5) Å3, Z = 4, Rgt(F) = 0.0522, wRref(F2) = 0.1274, T = 100.03(18) K.